The Influence Of School Principal Leadership, Work Motivation And Work Environment On The Competency Of Vocational Secondary School Teachers - Sari Nurhayati (International Journal of Management, Economic, Business and Accounting, 2023)
Purpose of the study — This study aims to examine the influence of school principal leadership, work motivation, and work environment on the competency of vocational secondary school teachers. The purpose is to understand the relationships and effects of these factors on the teachers' competency and provide insights for improving the quality of vocational educationResearch method—The research employed a quantitative approach using a survey questionnaire to collect data from vocational secondary school teachers. The questionnaire consisted of items related to school principal leadership, work motivation, work environment, and teacher competency. A sample of teachers from various vocational secondary schools was selected, and the collected data were analyzed using statistical techniques such as correlation and regression analysis.Result— The findings of the study indicate significant relationships and effects between the variables under investigation. School principal leadership was found to have a positive and significant influence on the competency of vocational secondary school teachers. Furthermore, both work motivation and work environment were identified as significant predictors of teachers' competency. Teachers who perceived strong leadership from principals, high levels of work motivation, and positive work environments demonstrated higher levels of competency in their teaching practices.Conclusion— Based on the results, it can be concluded that school principal leadership, work motivation, and work environment play crucial roles in shaping the competency of vocational secondary school teachers. Effective leadership from principals, combined with a motivating work environment, can enhance teachers' motivation and ultimately contribute to their professional growth and competence. These findings highlight the importance of creating supportive and inspiring work environments in vocational secondary schools.